Instrumentation of an ergometer to monitor the reliability of rowing performance - Macfarlane, D. J.; Edmond, I. M.; Walmsley, A. (Journal of Sports Sciences, 1997)
The aim of this study was to develop a portable data-acquisition system to measure the stroke-by-stroke power output and the force developed at the feet during simulated rowing, and to use the system to investigate the reliability of selected variables used to describe rowing performance. Using a Concept II rowing ergometer, the instantaneous power output was calculated as the product of the force at the handle, measured using a small transducer mounted near the handle, and the velocity of the handle, measured using an infra-red emitter-receiver to detect the passage of each vane of the flywheel. The cumulative force at the feet was measured using two force-plates, one mounted under each foot. The outputs from all transducers were sampled at 30 Hz using an 80386SX computer running Asyst data-acquisition software. Excellent linearity in all transducers was established and a calibration of the system revealed measurement errors of less than 3%. The reliability of the variables used to describe rowing performance was studied using a repeated 90 s maximal test on seven experienced oarsmen. Statistical analysis indicated that, of the 14 variables used, only two failed to meet the set criterion. In conclusion, it was found that a rower's performance during simulated rowing was very reliable and that the selected variables used in this study could be used to objectively describe performance on a rowing ergometer.